Reforming University Admissions in Vietnam - Le, Mai Thi Truc; Tran, Khue Van (International Higher Education, 2025)
<h3 id="this-paper-examines-the-evolution-of-vietnams-university-admission-system-over-the-past-three-decades-highlighting-key-reforms-aimed-at-improving-fairness-accessibility-and-educational-quality-the-study-explores-the-challenges-and-successes-of-each-reform-phase-emphasizing-the-shift-toward-competency-based-and-digital-assessments-it-supports-a-holistic-education-approach-to-training-university-students-in-meeting-the-needs-of-societal-development-and-reveals-an-effort-to-expand-opportunities-for-private-universities-within-the-system" data-pm-slice="1 1 []">This paper examines the evolution of Vietnam’s university admission system over the past three decades, highlighting key reforms aimed at improving fairness, accessibility, and educational quality. The study explores the challenges and successes of each reform phase, emphasizing the shift toward competency-based and digital assessments. It supports a holistic education approach to training university students in meeting the needs of societal development and reveals an effort to expand opportunities for private universities within the system.